Performance Evaluation of Bone Glue-Modified Asphalt - Asif Ali; Naveed Ahmad; Muhammad Adeel; Syed Bilal Ahmed Zaidi; Muhammad Sohail Jameel; Farsan Ali Qureshi; Waqas Haroon; Syeda Aamara Asif (Advances in Materials Science and Engineering)
Asphalt is one of the primary materials that are extensively used by the pavement industry throughout the world. Its behaviour is highly dependent on the amount of loading and the level of temperature it is exposed to. Asphalt has been modified in the past with different additives to improve its high- or low-temperature properties. In Pakistan, temperature remains high for most of the time of the year; hence, asphalt binders with less susceptibility to higher temperatures are preferred for flexible pavements. Acids, polymers, fibers, and extenders have been used by the researchers to improve high-temperature performance of asphalt mixture. In the present study, a bio material derived from the animal waste, named as bone glue (BG), has been used with the 60/70 penetration grade binder in dosages of 3%, 6%, 9%, and 12% by weight of asphalt binder. The bone glue is produced from a sustainable source. It is a cost-effective and eco-friendly material. Moreover, it produces a durable and nonhazardous asphalt composite. The influence of addition of bone glue on asphalt binder was evaluated using different testing techniques which include consistency tests, rheological analysis, and adhesion tests. Furthermore, different performance tests were conducted on bone glue-modified asphalt mixtures. Fourier-transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) analysis were carried out to ensure the homogeneity and proper mixing of bone glue in asphalt binder. The results from the tests reveal that bone glue stiffens the asphalt binder hence enhancing its high temperature performance. Bone glue dosage of 9% by weight of the binder was found to be the optimum dosage based on the rheological and performance analysis.